Rosemary oil nano-emulsion potentiates the apoptotic effect of mitomycin C on cancer cells in vitro - Waad Al-otaibi (Pensoft Publishers, 2021)
Purpose: To formulate nano-emulsified rosemary oil (REO/NE) and determine its effect on the anticancer agent, mitomycin C (MC) when used as a carrier for the drug. Methods: The droplet size of REO/NE was markedly enlarged when mixed with MC. The cytotoxicity of the formulations on HeLa and MCF-7 cells was determined using MTT assay. The combination index (CI) values were estimated with CompuSyn software, while apoptosis was determined using DAPI fluorescent dye. Results: Treatment of MCF-7 cells and HeLa cells with REO/NE (1% v:v and 1.33% v:v, respectively) reduced the IC50 of MC 33 and 15 folds, respectively. Under fluorescent microscopy, cells treated with REO/NE+MC had more marked reduction of the nuclear area than MC-treated cells. Conclusion: These results indicate that REO/NE is an efficient carrier for MC since it enhanced MC delivery and increased its effect on the cells through the induction of apoptosis at low concentrations of MC.